2019
DOI: 10.1039/c9ob00449a
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(ii)-catalyzed C(sp2)–H sulfuration/annulation with elemental sulfur: selective access to benzoisothiazolones

Abstract: The first Ni(ii)-catalyzed direct sulfuration/annulation of C(sp2)–H bonds with elemental sulfur was developed to afford structurally diverse benzoisothiazolones with benzimidazole skeletons in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Another strategy for the synthesis of benzoisothiazolone 252 based on o-CÀ H functionalization was studied (Scheme 88). [110] Although benzamides with unsubstitued o-positions could be used, the method requires 2-(N-methylbenzimidazolyl)isopropyl as an N, N-bidentate directing group. Furthermore, the use expensive nickel triflate catalyst, strong oxidant KMnO 4 and high molecular weight additive TBAI as well as high temperature under high pressure con- ditions makes the reactions less attractive as a synthetic method.…”
Section: Benzoisothiazolementioning
confidence: 99%
“…Another strategy for the synthesis of benzoisothiazolone 252 based on o-CÀ H functionalization was studied (Scheme 88). [110] Although benzamides with unsubstitued o-positions could be used, the method requires 2-(N-methylbenzimidazolyl)isopropyl as an N, N-bidentate directing group. Furthermore, the use expensive nickel triflate catalyst, strong oxidant KMnO 4 and high molecular weight additive TBAI as well as high temperature under high pressure con- ditions makes the reactions less attractive as a synthetic method.…”
Section: Benzoisothiazolementioning
confidence: 99%
“…Shi achieved a Cu‐mediated benzoisothiazolone synthesis using the (pyridin‐2‐yl)isopropylamine (PIP‐amine) bidentate directing group . Afterward, Gong and Song developed a catalytic variant adopting a Ni complex with the aid of 2‐amino alkylbenzimidazole (MBIP‐amine) directing group …”
Section: Methodsmentioning
confidence: 99%
“…Inspired by Shi's results of copper-mediated directing C-H sulfuration, 9a Song et al reported the first nickel-catalyzed direct sulfuration/annulation of C(sp 2 )-H bonds with elemental sulfur by using 2-amino alkylbenzimidazole (MBIP-amine) as a N,N-bidentate directing group (Scheme 52). 87 While the substrate scope of this reaction was well studied, to further demonstrate the practical applicability of this protocol, the resultant benzoisothiazolone products were transformed into other useful compounds such as thioethers and saccharin derivatives.…”
Section: S Liu Et Almentioning
confidence: 99%